Methodological aspects in Permit Project: the Italian experience - Roberto Melchiori; Rita Minello; Juliana Raffaghelli (Pensa MultiMedia, 2015)
The definition of what a good research methodology is varies according to initial assumptions, theories and philosophical approaches shared by researchers and based on the intended uses of the results of a research. In the Permit project the methodological approach adopted by the Italian research group has involved both quantitative and qualitative methods. More than that, studies using mixed-methods have shown that integration of these traditions within the same study can be seen as complementary. The present paper will examine the methodology chosen, which includes both the survey and the choices made for the design of the project. Such methodology can be regarded as an example of mixed-method approach.